Visible light absorption of TiO2 materials impregnated with tungstophosphoric acid ethanol–aqueous solution at different pH values. Evidence about the formation of a surface complex between Keggin anion and TiO2 surfaces - Rengifo Herrera, Julian Andres (2013)
TiO2 particles prepared by the sol-gel method were impregnated at different pH values (1.0, 2.0, 5.0 and 10.0) with a water-ethanol solution (50% V/V) of tungstophosphoric acid (TPA) (0.012 M). Similar preparation was carried out to synthesize TiO2 impregnated with [WO4] 2- (TiW). These materials were characterized by different techniques such as UV-vis diffuse reflectance spectroscopy (UV-vis DRS), magic angle spinning nuclear magnetic resonance of 31P (31P MAS NMR), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Fourier transform Raman spectroscopy (FT-Raman). Results revealed that TPA-TiO2 materials exhibit visible light absorption only when impregnation was done at pH 1.0 (TiTPA1) and 2.0 (TiTPA2). TiW powder did not show visible light absorption. XRD patterns show the presence of peaks at 2θ = 25.4 (1 0 1), 37.9 (0 0 4), 47.8 (2 0 0) and 54.3 associated to the anatase phase. Solid NMR, FT-IR and FT-Raman characterization showed that TiTPA1 and TiTPA2 samples contain Keggin ([PW12O40] 3-) and lacunary anions ([PW11O39] 7-) respectively. On the other hand, FT-Raman results revealed a blue shifting and broadening of the band at 141 cm-1 corresponding to anatase TiO2 and moreover, a broadening of bands at 900-1100 cm -1 attributed to Keggin structures of TPA. Both spectral changes could be related to the formation of a surface complex between the Keggin anion of TPA and TiO2 surfaces. This interaction should be responsible for visible light absorption